Transcription factor IRF8 orchestrates the adaptive natural killer cell response - Adams, Nicholas M. (Immunity, 2018)
Natural killer (NK) cells are innate lymphocytes that display features of adaptive immunity during viral infection. Biallelic mutations in IRF8 have been reported to cause familial NK cell deficiency and susceptibility to severe viral infection in humans; however, the precise role of this transcription factor in regulating NK cell function remains unknown. Here, we show that cell-intrinsic IRF8 was required for NK cell-mediated protection against mouse cytomegalovirus infection. During virus exposure, NK cells upregulated IRF8 through interleukin-12 (IL-12) signaling and the transcription factor STAT4, which promoted epigenetic remodeling of the Irf8 locus. Moreover, IRF8 facilitated the proliferative burst of virus-specific NK cells by promoting expression of cell cycle genes, and directly controlling Zbtb32, a master regulator of virus-driven NK cell proliferation. These findings identify the function and cell type-specific regulation of IRF8 in NK cell-mediated antiviral immunity, and provide a mechanistic understanding of virus susceptibility in patients with IRF8 mutations.